An experimental investigation on the performance of a vertical axis wind turbine in steady wind - Edwards, Jonathan Mark; Danao, Louis Angelo M.; Eboibi, Okeoghene
An experimental study was carried out into the performance of a wind tunnel scale vertical axis wind turbine (VAWT) under steady wind conditions. Wind speed tested was 7m/s, giving a Reynolds number of around 75,000. The power coefficient (CP) of the VAWT over a wide range of reveals a negative trough from = 1 up =3 with the lowest CP of -0.11 at =2.4. Beyond = 3 the CP rises to a maximum of 0.21 at * = 4.0 after which it falls close to zero at = 5. This CP profile is typical of the scale of the VAWT tested where a negative trough is present mostly due to high zero-lift drag that hampers the ability of the rotor to generate positive torque at low and self-start. The negative trough is observed to slowly diminish as wind speeds, and consequently, Reynolds number increases.
Keywords: Vertical axis wind turbine ( VAWT).; Rotor